The interplay among Th17 and T regulatory cells in the immune dysregulation of chronic dermatophytic infection. (February 2020) - Rai, Gargi; Das, Shukla; Ansari, Mohammad Ahmad; Singh, Praveen Kumar; Pandhi, Deepika; Tigga, Richa Anjleen; Bhattacharya, Sambit Nath; Gupta, Chhavi; Dar, Sajad Ahmad
Abstract: The delineation of the pathogenic interaction between the host skin immune responses and dermatophytes has remained indigent. The obscure enigma in host-dermatophyte immunopathogenic interactions is the T regulatory (Treg) and T-helper (Th) 17 cell role in maintaining immune homeostasis. We attempted to understand the regulation and recognition of lineage-specific response in chronic dermatophytic skin infection patients. The percentages of Th17 (CD4 + CD161 + IL23R + ) and Treg (CD4 + CD25 + FoxP3 + ) cell subpopulations in the peripheral circulation of thirty chronic dermatophytic skin infection patients and twenty healthy individuals was determined. The serum cytokine levels were estimated for disease correlation. The mean duration of the disease was 10.68 ± 8.72 months, with Trichophyton mentagrophytes complex as the major pathogen. Total serum IgE level of patients was significantly higher compared to healthy controls (305 ± 117 vs 98.53 ± 54.55 IU/ml; p < 0.01). Expression of Th17 and Treg cell markers on CD4 + T cells was significantly elevated in patients than controls ( p < 0.05). Comparatively, serum interleukin (IL)-4 and interferon (IFN)-γ levels were increased, with low IL-10 levels in patients. Our data envisages a complex immune dysfunction in chronic dermatophytosis, arising either as a result of dermatophyte exposure or paradoxical precedence of disease establishment. Designing new treatment strategies and preventing recurrences are challenges for future research. Highlights: Th17 and Treg expression was elevated in dermatophytosis patients than controls. Patient serum levels of IL-4 and IFN-γ were increased with decreased IL-10 levels. A complex immune dysfunction was observed in patients of chronic dermatophytosis.